Under the flags of freedom : slave soldiers and the wars of independence in Spanish South America - Blanchard, Peter, 1946- (Pitt Latin American series., 2008)
During the wars for independence in Spanish South America (1808-1826), thousands of slaves enlisted under the promise of personal freedom and, in some cases, freedom for other family members. Blacks were recruited by opposing sides in these conflicts and their loyalties rested with whomever they believed would emerge victorious. The prospect of freedom was worth risking one's life for, and wars against Spain presented unprecedented opportunities to attain it. Much hedging over the slavery issue continued, however, even after the patriots came to power. The prospect of abolition threatened existing political, economic, and social structures, and the new leaders would not encroach upon what were still considered the property rights of powerful slave owners. The patriots attacked the institution of slavery in their rhetoric, yet maintained the status quo in the new nations. It was not until a generation later that slavery would be declared illegal in all of Spain's former mainland colonies. Through extensive archival research, Blanchard assembles an accessible, comprehensive, and broadly based study to investigate this issue from the perspectives of Royalists, patriots, and slaves. He examines the wartime political, ideological, and social dynamics that led to slave recruitment, and the subsequent repercussions in the immediate postindependence era. Under the Flags of Freedom sheds new light on the vital contribution of slaves to the wars for Latin American independence, which, up until now, has been largely ignored in the histories and collective memories of these nations.